Odpowiedź :
Za literki podstawiamy podaną po prawej liczbę:
a) dla [tex]x=\frac{2}{3}[/tex]
[tex]8-(\frac{2}{3})^2=8-\frac{4}{9}=7\frac{9}{9}-\frac{4}{9}=7\frac{5}{9}[/tex]
b) dla [tex]a=-2[/tex]
[tex]5*(-2)+(-2)^2=-10+4=-6[/tex]
c) dla [tex]m=5[/tex]
[tex]2*5^2-3*5=2*25-15=50-15=35[/tex]
d) dla [tex]u=10[/tex]
[tex]10^3+2*10=1000+20=1020[/tex]
e) dla [tex]y=-\frac{1}{2}[/tex]
[tex]7*(-\frac{1}{2})+2*(-\frac{1}{2})^3=-\frac{7}{2}+2*(-\frac{1}{8})=-\frac{14}{4}-\frac{1}{4}=-\frac{15}{4}=-3\frac{3}{4}[/tex]
f) dla [tex]x=-3[/tex]
[tex]\frac{2+5*(-3)}{2-(-3)}=\frac{2-15}{2+3}=\frac{-13}{5}=-2\frac{3}{5}[/tex]
g) dla [tex]x=-1[/tex]
[tex]\frac{(-1)^2+2(-1+3)}{(-1)^2-2}=\frac{1+2*2}{1-2}=\frac{1+4}{-1}=-5[/tex]
h) dla [tex]x=2[/tex]
[tex]3*2-2^2-(2-3*2)=6-4-(2-6)=2-(-4)=2+4=6[/tex]